Analisis Harga Ikan Cakalang Terhadap Konsumsi Masyarakat Di Kota Manado - Jan, Arrazi Hasan (JURNAL RISET BISNIS DAN MANAJEMEN, 2017)
Skipjack fish is an important commercial fish. Although it is not currently threatened, the purse seine nets and other unsustainable methods used to catch skipjack fish. Skipjack fish have a streamlined body that mostly without scales. Their lower side and belly are silver with 4 to 6 dark bands. Skipjack fish is found worldwide in tropical and subtropical waters and is a highly migratory schooling species. Skipjack has become increasingly popular among chefs in recent years as a substitute for yellowfin tuna.Keywords: Skipjack Fish, Body, Tropical And Subtropical